Left Atrial Strain by 2D Speckle Tracking Echocardiography in Patients with Systemic Hypertension in Babylon Province - Ali Hamid Abbas Al-Murib; Hassan Salim Al-Jumaily; Zainab Falah Hassan; Shokry F. Al-Saad (Medical Journal of Babylon)
Background:Systemic hypertension is an expanding health problem and a major cause of cardiovascular morbidity and mortality. Left atrial (LA) strain by speckle tracking is a new echocardiographic modality that can detect impairment in LA function. Objectives:The aim was to analyze the parameters of LA strain in patients with systemic hypertension and compare them to those of normal persons. Materials and Methods:A case–control study was conducted at the echocardiography department of Marjan Medical City in Hillah from February 2023 to June 2023. The study focused on patients with hypertension and compared their 2D echocardiography, Doppler, tissue Doppler, left ventricle global longitudinal strain, and LA strain to those of a control healthy group. Data collection included a questionnaire, echocardiography using the GE Vivid iq machine, and statistical analysis using Statistical Package for the Social Sciences (SPSS) 27 software. Results:In total, 100 persons were enrolled in the study; 50 of them were patients with systemic hypertension, and the other 50 were persons with negative medical history. The two groups were age, gender, and body surface area matched. Echocardiographic parameters were compared, concentrating on LA strain and diastolic function parameters. A strong correlation was found between hypertension and LA strain parameters. Reservoir, conduit, and contractile strain were lower in the hypertensive group, while the LA volume and LA indexed volume were statistically larger in the hypertensive group than the control group, with a P value of less than 0.001 in both. Conclusion:LA strain by speckle tracking is affected in systemic hypertension more and even before the diastolic function affection. Earlier detection and treatment of dysfunction can delay or even prevent complications.